Solid phase transformation and stability of carbamazepine-saccharin co-crystal - Nazrul Shafeeq, Shahadan (2012)
Formulation of drug products is a multidisciplinary field, with pharmaceutical materials science being a fundamental branch that continuously provides important insights, theories, and technologies to formulation sciences. The recent advances in this area have brought this research possibility to produce pharmaceutical materials by crystallization design. This research is conducted to determine the character by both physical and chemical properties beside to determine the solubility of Carbamazepine and Saccharin. It is started by determine the co-crystal solubility of Carbamazepine and. Saccharin by applying the different concentration and temperature of Carbamazepine and Saccharin solution by following gravimetric method. It is proceed by determine the characterization of solution by screening using FTIIR, TGA and DSC to get morphology, melting point, weight loss and wavelength. The final discussion after result finding, it can be concluding that concentration and temperature are the main factor to control the solubility of Carbamazepine and Saccharin co-crystal. By using the solubility that was obtained from the gravimetric method, the characterization process of both Carbamazepine and Saccharin are also conclude by their own properties. As an additional conclusion, solid state form of active pharmaceutical ingredients (APIs), cocrystals not only offer a tool for tailoring physicochemical properties, but also create new opportunities for the research-based pharmaceutical companies to address intellectual property (IP) protection issues.